Japan Military Export Ban Lift in 2014 Under Shinzo Abe Administration - Rafyoga Jehan Pratama Irsadanar; Tulus Warsito (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2018)
This article analyzes Japanâ€™s interest in revoking its self-imposed military export ban in 2014 despite of its decades-long lucrative pacifism. The pacifism implementations includes partial and total military export ban, consecutively in 1967 and 1976. To puzzle out the question, this journal article utilized â€œBalance of Powerâ€ Concept by Morgenthau. This article found out that Shinzo Abe grand vision to transfer and export weaponries is balancing Peopleâ€™s Republic of China assertiveness in East China Sea by (1) reinforcing military alliances and (2) enhancing internal armaments. The alliances were strengthened by distributing weaponries to states in tension with Peopleâ€™s Republic of China and fortifying military industry cooperation with United States. The domestic military buildup was expected to escalate as arm export stimulated their domestic defense industry development. That includes the economic growth stimulus under Abenomics, in which also aimed to increase the military budget that leads to more robust defense.